Synthesis and evaluation of the antioxidant activity of new spiro-1,2,4-triazine derivatives applying Ag/Fe3O4/CdO@MWCNT MNCs as efficient organometallic nanocatalysts - Elham Ezzatzadeh; Somayeh Soleimani-Amiri; Zinatossadat Hossaini; Khatereh Khandan Barani (Frontiers in Chemistry, 2022)
We applied the Petasites hybridus rhizome water extract as green media so that Ag/Fe3O4/CdO@ multi-walled carbon nanotubes magnetic nanocomposites (Ag/Fe3O4/CdO@MWCNTs MNCs) could be prepared. We also evaluated its activity by using in the one-pot multicomponent reaction of acetophenones, diethyl oxalate, ammonium acetate, and activated carbonyl compounds such as ninhydrin, isatin and acenaphthylene-1,2-dione, and malononitrile and hydrazoyl chlorides in an aqueous medium at room temperature for the generation of spiro-1,2,4-triazines as new derivatives with tremendous output. Moreover, reducing organic pollutants from 4-nitrophenol (4-NP) was carried out by generating Ag/Fe3O4/CdO@MWCNTs in water at room temperature. The results displayed that Ag/Fe3O4/CdO@MWCNTs reduced pollutants of organic compounds in a short time. The synthesized spiro-1,2,4-triazines have NH and OH functional groups having acidic hydrogen with high antioxidant power. Also, the spiro-1,2,4-triazines exhibited antimicrobial ability. For this purpose, the disk diffusion method was applied and two kinds of bacteria, Gram-positive and Gram-negative, were employed for the analysis. Furthermore, we applied functional theory-based quantum chemical methods in order to better understand reaction mechanism density. To generate spiro-1,2,4-triazines, the applied process showed many properties such as reactions with short time, products with good yields, and simple extraction of catalyst from a mixture of reactions.